The Dynamics of Military-Police Relations in Post-Authoritarian Indonesia (1998 to 2020) - Yulianto, Bayu A. (Masyarakat: Jurnal Sosiologi, 2023)
Among myriad significant institutional changes in post-authoritarian Indonesia (1998-present) is the split of Indonesian police (POLRI) from the armed forces (ABRI, renamed into TNI after 1999). No longer locked in a dominant-subordinate configuration, the interaction between both institutions intensified in areas where they intersect. Drawing upon the theory of Strategic Action Field (SAF), this study attempts to capture the dynamics along the newly-established trajectory. It shall be argued that far from being one-dimensional, the relationship between both institutions has been marked by conflict, competition, and cooperation; depending on the SAF. Finally, this research proposes a new framework to assess the tendency of a particular TNI-POLRI interaction within a SAF by seeing the characteristics of the SAF itself, combined with the social skills of actors involved.